Quality Initiative to Reduce Catheter-Associated Urinary Tract Infections Using Cleansing Cloths With a Standardized Method. (October 2020) - Droske, Lauren; Patel, Parul; Schora, Donna; Patel, Jignesh; Barza, Ruby; Monsalud, Cherie Faith; Fisher, Adrienne; Lim, Rachel; Shah, Mona; Kufner, Bridget; Zelencik, Shane; Lavin, Mary Alice; et al.
Abstract : Background: Catheter-associated urinary tract infections (CAUTIs) account for >15% of hospital-acquired infections, resulting in increased length of stay and costs. Consequently, methods to improve indwelling urinary catheter (IUC) care and maintenance are warranted to reduce the risk of hospital-acquired CAUTIs. This study was a prospective quality improvement (QI) project to reduce CAUTIs using prepackaged cloths (ReadyCleanse by Medline Industries) and a simple, standardized cleaning process for care and maintenance of IUCs. Methods: This study is an ongoing QI project at NorthShore University HealthSystem, a 4-hospital system located north of Chicago, Illinois, with 750 beds and ∼64, 000 annual admissions. The study consists of a 1.5-month staff training on proper product use (phase 1), followed by an intervention using the cloths for IUC care (phase 2). Each package contains 5 individual cloths corresponding to a simple, 5-step, cleansing protocol. IUC care and maintenance are performed twice daily on a routine basis and after each incontinent episode. Beginning July 2018, current practice (soap and wash cloth) was replaced with the ReadyCleanse cloths, and on August 1, 2018, data collection began. Adult patients admitted at all 4 NorthShore Hospitals with an IUC for >24 hours are enrolled in the study. From patient electronic health records, we collected patient demographics, reason for IUC insertion, days of catheter use, and development of CAUTI (according to the NHSN definition). During the intervention, observations of compliance and performance of catheter care were also performed. For the analysis described here, results for the first 14 months of the study were compared to CAUTI numbers from the 14-month period prior to the start of the study (February 2017–March 2018); the data presented represent ∼50% of the planned data collection. Results: As of September 30, 2019, 4, 969 patients were prospectively enrolled in the study: 1, 491 patients from hospital A, 1, 451 from hospital B, 1, 091 from hospital C, and 936 from hospital D. Patient demographics for the study cohort were 47% female, with a median age of 77 years and an average of 3.9 catheter days per patient. Systemwide, observational audits for compliance using the cloths averaged 95%. Upon completion of study month 14, 22 CAUTIs had been identified, compared to 26 CAUTIs for the comparison period, indicating a 15% reduction. Conclusion: Implementation of this simple, standardized alternative for IUC care is feasible on a large scale and may have potential for reducing CAUTI rates. Funding: Medline Industries supported this study. Disclosures: None